2008
DOI: 10.1293/tox.21.175
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation of Galactosamine Hepatotoxicity by Albumin in Rats

Abstract: Abstract:The effect of rat albumin (RALB) on D-galactosamine (GalN) hepatotoxicity was investigated in male Crl:CD(SD) rats aged 6 weeks. The animals were divided into control, RALB, GalN, and RALB + GalN groups. GalN (800 mg/kg) was intraperitoneally administered immediately after an intravenous injection of RALB (100 mg/kg). The animals were euthanized 6 or 24 h later and subjected to laboratory investigations and histological examinations of the liver. Furthermore, in order to determine the contributing fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(34 reference statements)
0
0
1
Order By: Relevance
“…AST and ALT in rats administered a single dose of galactosamine at 1100 mg/kg are reported to be 100.86 and 121.57 U/mL, respectively [26]. AST and ALT in rats administered galactosamine at dose of 800 mg/kg are reported to be 96 and 199 U/ L, respectively [27]. AST and ALT showed higher values in this study than in hepatopathy model rats reported previously.…”
Section: Discussioncontrasting
confidence: 44%
“…AST and ALT in rats administered a single dose of galactosamine at 1100 mg/kg are reported to be 100.86 and 121.57 U/mL, respectively [26]. AST and ALT in rats administered galactosamine at dose of 800 mg/kg are reported to be 96 and 199 U/ L, respectively [27]. AST and ALT showed higher values in this study than in hepatopathy model rats reported previously.…”
Section: Discussioncontrasting
confidence: 44%